2017
DOI: 10.1016/j.knee.2017.08.059
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional analysis of accuracy of component positioning in total knee arthroplasty with patient specific and conventional instruments: A randomized controlled trial

Abstract: PSG led to adequate component positioning accuracy compared to the pre-operative plan. For the femoral component, the positioning was significantly closer to the planned position in the coronal plane, a similar trend was observed for the sagittal plane. But, for the tibial component, significantly more slope was introduced. A better prediction of component sizing was found with PSG compared to conventional surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 40 publications
1
21
0
Order By: Relevance
“…of patientsMean age (years)PSISIPSISIAbane et al [1]France5707067.8 (47–84)70.4 (54–83)Boonen et al [4]Netherlands7909069.0 ± 8.065.0 ± 8.8Boonen et al [5]Netherlands7909069.0 ± 8.065.0 ± 8.8Chareancholvanich et al [6]Thailand5404069.5 (55–84)70.3 (53–85)De et al [10]Belgium52024NRNRGan et al [13]China4353568.5 ± 4.867.8 ± 3.4Hamilton et al [15]USA4262668.1 (52–86)68.1 (52–86)Huijbregts et al [16]Australia5696466.7 ± 9.169.0 ± 9.6Khuangsirikul et al [20]Thailand34040NRNRKotela and Kotela [21]Poland54946…”
Section: Resultsmentioning
confidence: 99%
“…of patientsMean age (years)PSISIPSISIAbane et al [1]France5707067.8 (47–84)70.4 (54–83)Boonen et al [4]Netherlands7909069.0 ± 8.065.0 ± 8.8Boonen et al [5]Netherlands7909069.0 ± 8.065.0 ± 8.8Chareancholvanich et al [6]Thailand5404069.5 (55–84)70.3 (53–85)De et al [10]Belgium52024NRNRGan et al [13]China4353568.5 ± 4.867.8 ± 3.4Hamilton et al [15]USA4262668.1 (52–86)68.1 (52–86)Huijbregts et al [16]Australia5696466.7 ± 9.169.0 ± 9.6Khuangsirikul et al [20]Thailand34040NRNRKotela and Kotela [21]Poland54946…”
Section: Resultsmentioning
confidence: 99%
“…Patient-specific instrumentation has not yet been clearly demonstrated as effective in increasing the accuracy or precision of femoral component rotation: several studies have investigated the effect of PSI on rotational alignment and, with a few exceptions 8,27 , did not find statistical difference with respect to the outliers of femoral component rotation 14,15 and the accuracy in postoperative alignment of femoral rotation [12][13][14]20 . Two recent meta-analyses enrolled only 9 studies that reported femoral rotation as an outcome, and reached conflicting results: Thienpont et al concluded that no differences with regard to the rotational alignment are to be expected in the axial plane with the use of PSI, 28 whereas Huijbregts et al calculated the femoral rotation to be 0.45 more accurate with PSI 9 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a new technology that could reduce the proportion of incorrectly aligned implants appears appealing. However, there is controversy in the available published literature on the ability of PSI to affect the implant positioning, with some studies showing increased accuracy of femoral rotation with the use of PSI [8][9][10][11] and others revealing no differences from conventional alignment techniques [12][13][14][15][16][17][18][19][20] .…”
Section: Introductionmentioning
confidence: 99%
“…Seon et al [ 16 ] also reported accurate alignments provided by patient-specific guides without intraoperative complication in 38 knees, noting that severe varus deformity and osteophytes may interfere with seating of the guides. In a recent randomized controlled study on 50 patients comparing patient-specific and conventional instruments for the accuracy of component positioning in TKA [ 10 ], patient-specific guides provided more accurate component positioning and prediction of component sizing. Schotanus et al [ 17 ] reported that patient-specific cutting guides increases alignment of the femur component in partial to TKA revision surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Although patient-specific instruments have been used for TKA to be more efficient and cost-effective, many studies have shown controversial and inconsistent results on the efficiency and accuracy of TKA performed by using patient-specific cutting guides, mostly due to various 3D guide construction techniques or outcome measures that were used in the studies [ 1 ]. As most of the individual clinical studies reported the superiority of patient-specific instrumentation over conventional methods for providing limb alignment [ 2 , 10 ], meta-analyses failed to show significant difference between the 2 techniques [ 1 , 11 ]. In order to increase decisive evidence on the benefits and disadvantages of this innovative technique, more clinical studies are needed.…”
Section: Introductionmentioning
confidence: 99%